POLICY AND PRACTICE: REFLEKSI PERJANJIAN DAMAI HELSINKI 2005-2018: KESUKSESAN DAN TANTANGAN KEDEPAN - Aiyub Kadir, M. Ya'kub (Indonesia Social Justice Network (ISJN), 2019)
This paper is a reflection of the peace agreement between the Free Aceh Movement and the Government of Indonesia from 2005 to 2018. There have been improvement after a decade but there are still challenges that must be realized. The Helsinki Memorandum of Understanding (known as Helsinky peace agreement) on 15 August 2005 resulted a consensus that Aceh could have greater rights than before, as stipulated in the Law on Governing Aceh number 11/2006. Thus, Aceh has more authorities to redefine the political, economic, social and cultural status in the Republic of Indonesia system. This paper attempts to analyze this problem through a historical description of the movement of the Acehnese people, in the hope of contributing to increasing understanding of the concept of the Helsinki peace agreement in the context of sustainable peace and welfare improvement for the people of Aceh